2014
DOI: 10.15567/mljekarstvo.2014.0405
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of nonadditive genetic impacts on lifetime performance through a grading-up breeding program with Holstein-Friesian

Abstract: The aim of this study was to estimate the total lifetime milk production and non additive genetic effects (recombination and heterosis) of cows with different proportions of Holstein-Friesian genes, obtained from the Serbian Fleckvieh (SF) and the Holstein-Friesian (HF) crossbreeding program in Vojvodina. Upgrading of local breeds with the Holstein-Friesian breed in Vojvodina started in 1971 and continued 2008. Six genotypes of cows (F 1 , R 1 , R 2 , R 3 , R 4 , R 5 ) were obtained with increasing percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…An index including 305-day milk yield, peak yield, persistency of milk yield, and other economic traits of interest could be studied to introduce genes in Girolando cattle by crossbreeding. Nemes et al (2014) reported that a planned crossing leads to an optimal gene recombination, resulting in increases in production and maintenance of the variability necessary for a continuous positive success of selection of the observed properties. However, a negative recombination effect was found in the present study for all traits, except for LP and time to peak (TP, TP WD , and TP WL ).…”
Section: Breed Heterosis and Recombination Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…An index including 305-day milk yield, peak yield, persistency of milk yield, and other economic traits of interest could be studied to introduce genes in Girolando cattle by crossbreeding. Nemes et al (2014) reported that a planned crossing leads to an optimal gene recombination, resulting in increases in production and maintenance of the variability necessary for a continuous positive success of selection of the observed properties. However, a negative recombination effect was found in the present study for all traits, except for LP and time to peak (TP, TP WD , and TP WL ).…”
Section: Breed Heterosis and Recombination Effectsmentioning
confidence: 99%
“…Most studies report negative values for the recombination effect (Madalena et al, 1990;Nemes et al, 2014;Birhanu et al, 2015). Facó et al (2008) reported significant and negative recombination effects for MY and MY 305 traits in Holstein × Gyr crossbred cows, indicating that the gene recombination observed in some types of crosses produces depressant effects on milk production.…”
Section: Breed Heterosis and Recombination Effectsmentioning
confidence: 99%
“…Ao se misturar muitos cromossomos de origens diferentes, os organismos passam a misturá-los e formar novos cromossomos homólogos no fenômeno do crossing over que pode ocorrer nas células gaméticas e transferir para a próxima geração a recombinação genética (CARROLL, 2013;MATHER, 1938). O que é um efeito economicamente ruim a curto prazo, por trazer perdas na capacidade produtiva de certas características em diversas espécies de interesse comercial (DALTRO et al, 2021;MADALENA et al, 1990;NEMES et al, 2014), porém esta perda de produção é justificável ao se avaliar no longo prazo que ela permite um aumento da variabilidade genética dentro da população sem a inserção de novos indivíduos (BATTAGIN et al, 2016;GORJANC et al, 2017). Evitando dessa forma resultados indesejáveis como o efeito Bulmer (BULMER, 1971), que ocorre ao se focar em uma gigantesca propagação de material genético dos poucos touros superiores, reduzindo o tamanho efetivo da população (SHEN et al, 2018) e aumentando a endogamia.…”
Section: Recombinação Genéticaunclassified